Supercilliary madarosis in an Indian male with Chronic Myelogenous Leukemia Treated with Dasatinib - A case report - Gupta, Sahil; Bhatt, M L B; Kumar, Siddhartha; Batra, Ankit; Katepogu, Pranay (Indian Journal of Case Reports, 2016)
Dasatinib, a second generation multi-target tyrosine kinase inhibitor (TKI) is active against many imatinib-resistant BCR-ABL mutant forms, Src, and c-Kit tyrosine kinases. While skin hypopigmentation is a well recognized adverse effect of first generation TKIs; it has rarely been reported with dasatinib. We report a rare case of diffuse cutaneous hypopigmentation and bilateral supercilliary madarosis induced by dasatinib. A 51 year-old Indian male with no co-morbidities and with history of chronic myelogenous leukaemia with complex variant of Philadelphia translocation and E 225 V mutation in P loop domain of bcr-abl transcript who was initiated on imatinib followed by dasatinib as a part of treatment. After 5 months of treatment with dasatinib, he developed supercilliary madarosis bilaterally. Cutaneous side effects may adversely affect patient’s quality of life and, therefore, require prompt attention to prevent long-term complications or suboptimal outcomes due to poor compliance.